Evolution of Machine Learning Algorithms A Comprehensive Review - Lakshmi, D. Venkata (AG Volumes, 2024)
Machine learning (ML) enables machines to process and interpret large datasets, providing efficient solutions where traditional methods fall short. As data availability increases, the demand for ML grows across various industries to extract valuable insights. ML is a multidisciplinary field with diverse research areas aimed at teaching machines to learn from data without explicit programming. This review paper discusses the evolution of machine learning algorithms, including supervised, unsupervised, and reinforcement learning techniques. It also explores the applications of machine learning in different sectors. The paper highlights the progress of ML algorithms, their types, and their growing impact on data-driven decision-making.